Delta Time Company : a feasibility study on establishing watch making business - Agbuya, Precious C.; Fabonan, John Carlo F.; Gocuyo, Isaac Miguel S.; Lamac, Aizzielle Joy S.; Ligaya, Wndy M.; Lobo, Raldy Carl Y.; Ramirez, Ryu Charie S. and Reyes, Precious Catherine C. 4 0 16; 5
u
Feasibility Study: (Bachelor of Science in Accountancy) Pamantasan ng Lungsod ng Maynila, 2014.
Keywords: 2 -- 0; 6; 20; 20; 2